Pengembangan E-Modul Berbasis Android Sebagai Media Pembelajaran Bimbingan Teknologi Informasi dan Komunikasi pada Sekolah Menengah Pertama (SMP) - Handiswan Handiswan; Hasanah Nur; Anas Arfandi (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to develop an e-module based on android as a learning media for information and communication technology guidance in junior high schools that is valid, practical, and effective in improving student learning outcomes. The development model used is 4D which includes: Define, Design, Develop, and Disseminate. The research subjects were students of class VII with details: 5 students for one to one test at UPT SMPN 1 Duampanua, 10 students for small group testing at UPT SMPN 1 Duampanua, and 22 students for large group testing at UPT SMPN 5 Duampanua. The results showed that (1) The valid e-module was used based on the value of the media expert of 88.46 in the very valid category and the material expert of 90.05 in the very valid category; (2) The practical e-module is used with a score from the teacher of 87.53 in the very practical category, students of 86.66 in the very practical category, and observers of 87.46 in the very practical category, and (3) N- Gain score from the pre-test and post-test results was 0.71 with the high category, so it can be said that e-module based android is effective in improving learning outcomes of information and communication technology guidance.